2020
DOI: 10.7150/thno.46001
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear MYH9-induced CTNNB1 transcription, targeted by staurosporin, promotes gastric cancer cell anoikis resistance and metastasis

Abstract: Rationale: Peritoneal metastasis predicts poor prognosis of gastric cancer (GC) patients, and the underlying mechanisms are poorly understood. Methods: The 2-DIGE, MALDI-TOF/TOF MS and single-cell transcriptome were used to detect differentially expressed proteins among normal gastric mucosa, primary GC and peritoneal metastatic tissues. Lentiviruses carrying shRNA and transcription activator-like effector nuclease technology were used to knock down myosin heavy chain 9 (MYH9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 45 publications
3
101
0
Order By: Relevance
“…It promotes the tumorigenesis and development of those cancers and has a positive correlation with the prognosis of patients. Recently, it was confirmed that MYH9 binds to the CTNNB1 promoter to promote CTNNB1 transcription, conferring resistance to anoikis in gastric cancer [ 17 ]. Targeting MYH9 blocked HBX-induced GSK-3β ubiquitination to activate the β-catenin destruction complex, suppressing hepatocellular cancer stemness and the epithelial-to-mesenchymal transition [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It promotes the tumorigenesis and development of those cancers and has a positive correlation with the prognosis of patients. Recently, it was confirmed that MYH9 binds to the CTNNB1 promoter to promote CTNNB1 transcription, conferring resistance to anoikis in gastric cancer [ 17 ]. Targeting MYH9 blocked HBX-induced GSK-3β ubiquitination to activate the β-catenin destruction complex, suppressing hepatocellular cancer stemness and the epithelial-to-mesenchymal transition [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…MYH9, a class of MYH9 gene encoding “gastric” framework-related protein, is a hexamer composed of two 220 kDa heavy chains, two 17 kDa essential light chains, and two 20 kDa regulatory light chains, widely expressed in cells and tissues [ 78 80 ]. MYH9 has been confirmed to have vital regulatory effects in papillary thyroid cancer [ 81 ], osteosarcoma [ 82 ], gastric cancer [ 83 ], melanoma [ 84 ] and other diseases. However, the role of MYH9 in OA remains unknown previously.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, although the expression of MYH9 was not significantly different between LNCaP and LNCaP-AI cells, it increased in the cytoplasm while decreased in the nucleus of LNCaP-AI cells. Nuclear MYH9 acts as a transcription factor and binds to the promoter of CTNNB1 ( 52 ), suggesting the function of nuclear MYH9 is different from the common cytoplasmic ones that acts as scaffold protein promoting cell migration and invasiveness. We speculate that increased cytoplasmic MYH9 interacts with F-actin and other cytoskeleton proteins promoting cell migration and invasiveness while decreased levels of nuclear MYH9 reduce nuclear p53 accumulation.…”
Section: Discussionmentioning
confidence: 99%